Efektivitas implementasi kurikulum merdeka dalam pembelajaran PAI Di Sekolah Dasar Negeri - Indah Firda Fauziah (SAP (Susunan Artikel Pendidikan), 2025)
This study aims to identify the implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) at SDN Jurang Manggu Timur 02 using a descriptive quantitative research method. Data were collected through structured interviews with PAI teachers and observations of the learning activities. The results indicate that the Merdeka Curriculum has been effectively implemented through strategic steps such as initial assessments of students' characteristics, the development of teaching modules based on student needs, and the application of innovative teaching strategies like discovery learning, problem-based learning (PBL), and project-based learning (PjBL). These methods have proven effective in engaging students and enhancing their critical thinking skills. Furthermore, the study found that students' character development aligned with the Pancasila Student Profile was reinforced through religious habituation activities, such as communal prayers and Yasin recitation. This research contributes to the development of educational theory by emphasizing the importance of collaboration between schools, teachers, and parents in implementing the Merdeka Curriculum. Such collaboration plays a vital role in creating a supportive learning environment that addresses students' spiritual and moral needs, resulting in a more holistic educational experience.